2022
DOI: 10.1037/spq0000492
|View full text |Cite
|
Sign up to set email alerts
|

The roles of resilience, peer relationship, teacher–student relationship on student mental health difficulties during COVID-19.

Abstract: The present cross-sectional study aimed to (a) expand our understanding of the role of risk and resilience factors for adolescent adjustment during coronavirus disease (COVID-19) and (b) examine personal resilience, peer and teacher-student relationships as protective factors against mental health difficulties. A total of 3,662 students from 4th to 11th grades in Urumchi, China completed a survey in June 2020. Urumchi is an ethnically diverse city, with nearly 40% of the population in this school district bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 73 publications
0
21
0
3
Order By: Relevance
“…The community PCEs sub-dimension included multiple items focused on school and supportive interpersonal relationships established through school (e.g., support from friends and teacher). The stronger correlation between community PCEs and adult flourishing may, in part, be explained by the critical role of school for Chinese children and adolescent and the significance of school interpersonal relationships in child development, mental health, school adjustment, academic engagement, school satisfaction, and psychological well-being which may in turn promote flourishing in adulthood [ 65 , 66 , 67 , 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…The community PCEs sub-dimension included multiple items focused on school and supportive interpersonal relationships established through school (e.g., support from friends and teacher). The stronger correlation between community PCEs and adult flourishing may, in part, be explained by the critical role of school for Chinese children and adolescent and the significance of school interpersonal relationships in child development, mental health, school adjustment, academic engagement, school satisfaction, and psychological well-being which may in turn promote flourishing in adulthood [ 65 , 66 , 67 , 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…One candidate could be the additional challenges that COVID-19 brings for new seventh-graders’ transition to middle school. For example, a recent study among Chinese elementary, middle, and high school students showed that seventh grade marked the beginning of the decline of students’ resilience, and the seventh graders reported much lower score than students in the elementary school ( Zhu et al, 2022 ). As a result, seventh graders in our study may not have sufficient resilience to serve as a buffer for stressful life events.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the quality of peer relationship also did not provide a buffer from the negative impact of COVID-19-related stressful events on their mental health. The buffering role of peer support has been mixed among recent studies in times of COVID-19 ( Campione-Barr et al, 2021 ; Ellis et al, 2020 ; Zhu et al, 2022 ), perhaps due to adjustment in preventive policies (e.g., physical distancing, face covering) that affect the quality of maintaining meaningful and sustained support. More studies are needed to unpack different factors impacting the dynamics of peer support and its contributions to adolescents’ mental health during times of pro-longed stress.…”
Section: Discussionmentioning
confidence: 99%
“…Esta situación pudo intensificar el malestar y sus consecuencias en las víctimas del ciberacoso, quienes podrían llegar a sentirse más aisladas y vulnerables, provocándoles un mayor desajuste psicológico y emocional (Zych et al, 2019). Sin embargo, aún son escasos los estudios que hayan explorado dicha situación y sus consecuencias (Babvey et al, 2021;Zhu et al, 2021), y ninguno de ellos ha explorado las características de los adolescentes que son víctimas de ciber-rumor. Estudios transversales y longitudinales realizados durante el periodo de confinamiento han encontrado un aumento en los niveles de depresión, ansiedad y estrés entre los adolescentes, siendo mayores para las chicas (Magson et al, 2021;Panchal et al, 2021;Tamarit et al, 2020).…”
Section: Cibervictimización Y Síntomas Internalizantesunclassified
“…Explorar si una gestión adecuada de la situación y de su propia respuesta emocional podría minimizar el impacto en el bienestar de la víctima es objeto de investigación de este estudio. Por otro lado, la resiliencia adquiere un valor relevante por su posible papel reductor del impacto emocional durante el confinamiento, cuyo efecto traumático es diverso, posiblemente dependiendo del uso de estrategias y recursos personales para gestionar la adversidad (Zhu et al, 2021).…”
Section: Resiliencia Como Potencial Mediadorunclassified